Analisis Perkuatan Cerucuk Kayu Bakau Dan Kayu Mahang Terhadap Peningkatan Daya Dukung Tanah Gambut - Saputra, Adetia; Muhardi, Muhardi; Fatnanta, Ferry (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Riau province has a very large peatland. Large peatland is constraint in the development of infrastructure of a region. The problems posed ini the field of contruction is the amount of land degradation and low soil carrying capacity. Therefore, an alternative to the soil reinforcement is required by using the cerucuk timber to increase the carrying capacity of the foundation and soil reinforcement. This research was conducted to determine the carrying capacity of mangrove and mahogany wood as reinforcement on peat soil with laboratory scale modeling. The research was done by applying load tests on those timbers in a testing basin with dimensions of 1,2 m x 1 m x 1 m with variations of single pile, group pile consists of 4 piles, and group pile consists of 9 piles. The used method was alpha method as the reference to determine limit bearing capacity. From the test result of settlement interpretation loading of 25 mm on mangrove, it was obtained that maximum bearing capacity were 16,22 kg and 19,85 kg when the pile was embedded for 1 day and 7 days long. As for the mahang, the maximum bearing capacity were 15,51 kg and 18,47 kg when the pile was embedded for 1 day and 7 days long. According to the results, it could be concluded that mangrove piles had a larger bearing capacity compared to mahang piles.Keywords : mangrove piles, mahang piles, foundation`s bearing capacity, peat.